Hubungan antara Pola Asuh Islami Orang Tua terhadap Motivasi Belajar Siswa X Wates - Uliya Latifah Safrudin; Zahro Varisna Rohmadani (EduInovasi: Journal of Basic Educational Studies, 2024)
This study aims to examine the relationship between Islamic parenting patterns of parents and students' learning motivation at SMK X Wates. This study is motivated by the importance of the role of parents in shaping children's learning motivation, especially in the context of education based on Islamic values. The research method used is quantitative with a survey approach, where data is collected through questionnaires given to students. The population used for this study was 150 students. Then the data obtained were analyzed using statistical techniques to see the relationship between Islamic parenting patterns and learning motivation. The results of the study obtained an asymp sig-2 tailed value of .074 <0.05 which indicates that there is a significant relationship between Islamic parenting patterns of parents and students' learning motivation. This study is expected to provide insight for parents to apply effective parenting patterns in increasing children's learning motivation.